2012
DOI: 10.2131/jts.37.1059
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity evaluation of symmetrically branched glycerol trimer in human hepatocellular carcinoma HepG2 cells

Abstract: -An appropriate balance between lipophilicity and hydrophilicity is necessary for pharmaceuticals to achieve fine Absorption, Distribution, Metabolism and Excretion (ADME) properties including absorption and distribution, in particular. We have designed and proposed symmetrically branched oligoglycerols (BGL) as an alternative approach to improve the lipophilic-hydrophilic balance. We have previously shown that stability in circulation and water-solubility of such molecules as proteins, liposomes and hydrophob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…These results demonstrated that acute toxicities on tissues including hepatotoxicity of BGL003 should be as low risk causing as glycerol, which is widely used in miscellaneous commodities around us including foods and medicines, if it exists. It is quite consistent with our result in the accompanying paper that BGL003 did not show significant cytotoxicity against human hepatocarcinoma HepG2 cells (Miyamoto et al, 2012). Our data above suggest adequate tolerability of BGL003 in vivo.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…These results demonstrated that acute toxicities on tissues including hepatotoxicity of BGL003 should be as low risk causing as glycerol, which is widely used in miscellaneous commodities around us including foods and medicines, if it exists. It is quite consistent with our result in the accompanying paper that BGL003 did not show significant cytotoxicity against human hepatocarcinoma HepG2 cells (Miyamoto et al, 2012). Our data above suggest adequate tolerability of BGL003 in vivo.…”
Section: Resultssupporting
confidence: 93%
“…1E) (Nemoto et al, 2012c;Miyamoto et al, 2012). We recently noticed that the BGL003-conjugated fenofibrate yielded an active form of fenofibrate, fenofibric acid (Fig.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Cell viability was evaluated by MTT ((3 -(4,5 -di-methylthiazol-2yl)-2,5-diphenyltetrazolium bromide) assay as previously described (12,19,21).…”
Section: Evaluation Of Viabilitymentioning
confidence: 99%
“…Membrane permeability is correlated with lipophilicity, usually estimated using the logarithm of the n -octanol/water partition coefficient (log Po/w) [32]. The log Po/w of γ-oryzanol has been calculated as 12.1 using the XLOGP3 method [33], while that of fenofibrate, one of the most lipophilic agents among the clinically-used drugs, is 5.19 [34, 35]. This suggests that γ-oryzanol should be lipophilic enough to be membrane permeable and thus may influence intracellular metabolism.…”
Section: Impact Of a Brown Rice-derived Bioactive Product On Feeding mentioning
confidence: 99%